Stress Experienced by Stroke Survivors and Spousal Caregivers During the First Year After Discharge from Inpatient Rehabilitation - Ostwald, Sharon K. (2009)
PURPOSE: This study describes levels of stress in stroke survivors and spousal caregivers and identifies predictors of stress in couples during their first year at home. METHOD: The perceived Stress Scale (PSS) was administered to 159 stroke survivors and caregivers at discharge, 3, 6, 9, and 12 months. Other variables tested included stroke survivor function (FIM), health status, mutuality, stroke impact (SIS), caregiver coping (F-COPES), support (MOS Social Support Survey), and preparedness. Repeated measures analyses of PSS scores were conducted with linear mixed models for stroke survivors and caregivers. RESULTS: PSS scores for stroke survivors and caregivers were positively correlated (p<.01). Scores decreased significantly over the year, but caregivers had higher scores initially and decreased less. Stroke survivor function was a significant predictor of stress for both survivors and caregivers. Preparation was the most powerful predictor of stress in caregivers, while mutuality was the strongest predictor for stroke survivors. Good health, social support and coping were associated with less stress. CONCLUSIONS: Stress is increased by poor function and mediated by internal and external buffers including health, the dyadic relationship, coping ability and social support. More research using a dyadic research approach is needed to better understand stress within couples.